Measuring and Classifying Levels of Futures - Alexandre Costa-Leite (Философия и космология, 2023)
This is a paper dealing with methodological and foundational issues in the realm of Futures Studies. It provides possible metrics for the temporal coordinate in the cone of plausibility. As a consequence, some adaptable scales to classify levels of future with respect to a certain time interval relevant to measure the future of humanity are suggested.